Keragaman Kondisi Salinitas Pada Lingkungan Tempat Tumbuh Mangrove di Teluk Kupang, NTT - jeriels matatula (Jurnal Ilmu Lingkungan, 2019)
Mangrove forest ecosystems are  habitat of various types of microorganisms, but now, problems of mangrove forests experience are in quality and wealth. Efforts to rehabilitate activities  mangrove forests againts had been carried out but the results shown had not been maximized, so it is need the correct strategies  to achieve the success for rehabilitation activities. The studied was conducted in Teluk Kupang, East Nusa Tenggara, covered coastal areas of Kupang's mangrove forests and coastal mangrove forests in Kupang district. The method used in this studied was a systematic sampling method that was systematically distributed across all the mangrove forest areas. The method used for salinity measurement was  method of transmission and Transect Line Plots. Measurements was made in straight line and the size of the plot is 10 m x 10 m, the distanced between lines was 50 meters so that  total lane is 547 with the number of plots of observation 1641 plots. The value of  measurement results was made into the spread of salinity used the interpolation method. The condition of the crossed of  mangrove forest located on  coastal panoramas of  Kupang city shows a salinity value of 10,26 - 26.33%, while  salinity conditions was on the coast of  Kupang ten district 10-42.33 ‰. The salinity condition was formulation of the environmental conditions  mangrove forest on  coast of the island as well as attempts to support  management of mangrove forest activities. The distribution of different mangrove forest conditions along the coastal zone of North Sumatra shows an environmental condition that supports mangrove growth even though in some places the salinity values are high. Results of this study of salinity conditions is a study of the environment of mangrove growth so that it can provide an overview for the government in conducting various activities to rehabilitate mangrove forests.